2019
DOI: 10.3390/ijerph16050721
|View full text |Cite
|
Sign up to set email alerts
|

A Community-Based Intervention for Improving Medication Adherence for Elderly Patients with Hypertension in Korea

Abstract: The chronic disease management program, a community-based intervention including patient education, recall and remind service, and reduction of out-of-pocket payment, was implemented in 2005 in Korea to improve patients’ adherence for antihypertensive medications. This study aimed to assess the effect of a community-based hypertension intervention intended to enhance patient adherence to prescribed medications. This study applied a non-equivalent control group design using the Korean National Health Insurance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 48 publications
(61 reference statements)
0
10
0
1
Order By: Relevance
“…The previous study from other area in Indonesia found that PROLANIS is effective to control BP through health status monitoring, club activity, home visit, and education on the eating pattern and physical activities programs [7]. Other studies from Korea also showed that population-based intervention is beneficial in improving hypertensive patients' adherence to medication [8]. Lu et al also concluded that population-based hypertension intervention could help improving BP control, especially the intervention involving interactive session; this method was more effective compared to self-study and classical lecture [9].…”
Section: Discussionmentioning
confidence: 98%
“…The previous study from other area in Indonesia found that PROLANIS is effective to control BP through health status monitoring, club activity, home visit, and education on the eating pattern and physical activities programs [7]. Other studies from Korea also showed that population-based intervention is beneficial in improving hypertensive patients' adherence to medication [8]. Lu et al also concluded that population-based hypertension intervention could help improving BP control, especially the intervention involving interactive session; this method was more effective compared to self-study and classical lecture [9].…”
Section: Discussionmentioning
confidence: 98%
“…The ending Eclampsia project in Nigeria showed community health extension workers at primary health care facilities can correctly measure BP, detect high BP, and treat accordingly for severe pre-eclampsia and eclampsia [ 52 ]. In Korea, a community-based interventions led by CHWs have shown promising results in early detection of hypertension, linkage to health facilities, improved medication adherence, and BP control [ 53 ]. Similarly, a study conducted in low and middle income countries confirmed that CHWs can detect and treat individuals with hypertension and other priority chronic diseases with proper training, supervision and logistical support [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our researchers, who had participated in the planning and evaluating Hongcheon-gun Hypertension and Diabetes Registration and Education Program for the past eight years [ 78 , 79 ], finally selected two opposing views of community-based intervention programs as policy alternatives to the AHP evaluation model that faced new challenges amid drastic changes in health policies in Korea. Unlike other AHP studies [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ], this study largely had a three-step mixed process.…”
Section: Discussionmentioning
confidence: 99%